Javanese Philosophical Narratives in New Media: Analysis Semiotics Frans Magnis YouTube Content Suseno - Rafli Kahfi; Abrar M. Dawud Faza; Sholahuddin Ashani (Sufiya Journal of Islamic Studies, 2025)
The development of social media has created a new space for the dissemination of philosophical discourse. This study aims to examine how the narrative of Javanese philosophy is constructed in the YouTube content of Frans Magnis Suseno. The method used is semiotic analysis based on Roland Barthes' approach, which distinguishes between denotative, connotative, and mythic meanings in both visual and verbal texts. The analysis reveals that Frans Magnis conveys core values of Javanese philosophy such as eling, nrimo, and sumeleh through simple, communicative narratives adapted to today's social context. These narratives not only popularize Javanese philosophy but also make it more accessible to younger generations through a modern visual format. This study highlights the significant potential of new media in transforming traditional discourses into a more inclusive digital domain.